KORELASI ANTARA MOTIVASI DAN MINAT BELAJAR DENGAN HASIL BELAJAR TEMATIK KELAS V SDN - Annisa, Nolla; Kresnadi, Hery; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This study aims to describe whether there is a correlation between learning motivation and learning interest with learning outcomes in the thematic learning of class V SDN Clusters X Sungai Kakap Kubu Raya. The research method used is descriptive research correlation study form. The population in this study were 121 students of Sungai Kakap Elementary School in 121 students. The sample in the study were 41 students who were determined by purposive sampling technique, namely the VA class of SDN 18 Sungai Kakap totaling 22 students and the VB class of SDN 27 Sungai Kakap totaling 19 students. The results showed learning motivation of 75.21%, learning interest of 75.33%, and learning outcomes obtained an average of 76.41. Statistical calculations using the product moment correlation formula namely learning motivation with learning outcomes obtained rcount of 0.477 and learning interest with learning outcomes obtained rcount of 0.441. For motivation and interest in learning with learning outcomes using the multiple correlation formula obtained by 0.489 included in the category of moderate relationships with Fcount of 5.97 and Ftable ? = 5% of 3.25 which means Fhitung (5.97)> Ftable (3.25) , then Ha is accepted. So, it can be concluded that there is a relationship between learning motivation, learning interest and learning outcomes in the thematic learning of fifth grade students of SDN Clusters X Sungai Kakap Kubu Raya. Keywords: Correlation, Learning Motivation, Learning Interest, Learning Outcomes, and Thematic Learning